Freedom of Expression vs Political Stability: Legal Interpretation of Commotion in Social Media After the Issuing of a Constitutional Court Decision - Zaka Firma Aditya; Sholahuddin Al-Fatih (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the study: This article analyzes the tension between freedom of expression and political stability in the context of the Indonesian Constitutional Court’s Decisions No. 90/PUU-XXI/2023, 78/PUU-XXI/2023, 7/PUU-VII/2009, and 50/PUU-VI/2008 on the Dissemination of Information Via Social Media, which are deemed to potentially inducing commotion. Methodology: This article used legal research methods using the statutory, conceptual, and case approaches. The legal materials were examined through a prescriptive analysis to identify new normative constructions related to the cyber commotions, as interpreted in the Constitutional Court decision. Results: The article's main findings show that the Court tends to acknowledge the dangers of vague and ambiguous-norms and relates this issue to the principle of legality, legal certainty, and the permissible limitations of rights under the International Covenant on Civil and Political Rights. The Court underscores the importance of normative clarity to ensure that such provisions do not become repressive instruments against political expression or criticism in digital spaces. In an era where public discourse largely takes place in the digital-space, criminalization based solely on the potential for commotion, without objective criteria, may hinder citizens’ participation in democracy. Results: This article recommends reformulating the norms by employing a more contextual, human rights-based approach to prevent the misuse of law that suppresses freedom of expression. A proportional balance between freedom of expression and political stability can be achieved within Indonesia’s legal system. The scholarly contribution of this research will greatly assist researchers in understanding the meaning of the freedom of expression on social media and will support stronger law enforcement. Novelty/Originality of this Study: The Constitutional Court's Decision on the Judicial Review of Articles 28(3) and 4A(3) of Law 1/2024 emphasizes the need of exercising prudence while balancing the protection of freedom of expression with measures to maintain public order. Keywords: Constitutional Court; Decision; Cyber; Commotion.   ABSTRAK Tujuan penelitian: Artikel ini menganalisis ketegangan antara kebebasan berekspresi dan stabilitas politik dalam konteks putusan Mahkamah Konstitusi Indonesia Nomor 90/PUU-XXI/2023, Nomor 78/PUU-XXI/2023, Nomor 7/PUU-VII/2009, dan Nomor 50/PUU-VI/2008 tentang penyebaran informasi melalui media sosial yang dianggap berpotensi menimbulkan keresahan. Metodologi: Artikel ini menggunakan metode penelitian hukum dengan pendekatan undang-undang, konseptual dan kasus. Bahan hukum dianalisis menggunakan analisis preskriptif untuk menemukan norma baru terkait dengan keresahan siber yang telah ditafsirkan dalam Keputusan Mahkamah Konstitusi. Hasil: Temuan utama artikel ini menunjukkan bahwa Mahkamah cenderung mengakui bahaya norma yang samar dan multitafsir, serta mengaitkan masalah ini dengan asas legalitas, kepastian hukum, dan pembatasan hak yang diperbolehkan berdasarkan Kovenan Internasional tentang Hak Sipil dan Politik (ICCPR). Mahkamah menggarisbawahi pentingnya kejelasan norma agar ketentuan tersebut tidak menjadi alat represif terhadap ekspresi politik atau kritik di ruang digital. Di era di mana wacana publik sebagian besar terjadi di ruang digital, kriminalisasi yang semata-mata didasarkan pada potensi kerusuhan, tanpa kriteria yang objektif, dapat menghambat partisipasi warga negara dalam demokrasi. Kegunaan penelitian ini: Artikel ini merekomendasikan perumusan ulang norma menggunakan pendekatan yang lebih kontekstual dan berbasis hak asasi manusia untuk mencegah penyalahgunaan hukum yang menekan kebebasan berbicara. Keseimbangan proporsional antara kebebasan berekspresi dan stabilitas politik dapat dicapai dalam sistem hukum Indonesia. Kontribusi keilmuan dari penelitian ini akan sangat membantu para peneliti dan akademisi dalam memahami makna kebebasan berekspresi di sosial media dan akan membantu penegakan hukum yang kuat. Kebaruan/Keaslian Kajian: Putusan Mahkamah Konstitusi tentang pengujian Pasal 28 ayat (3) dan Pasal 45A ayat (3) UU No. 1 Tahun 2024 menegaskan perlunya kehati-hatian dalam menyeimbangkan upaya perlindungan kebebasan menyampaikan pendapat dengan upaya menjaga ketertiban umum. Kata kunci: Mahkamah Konstitusi; Putusan; Siber; Kerusuhan